1995
DOI: 10.2166/wst.1995.0209
|View full text |Cite
|
Sign up to set email alerts
|

The transfer of solids in combined sewer networks

Abstract: Suspended solids are the main vectors of pollution in combined sewer wet weather flows. In spite of being very fine, they decant rather quickly except in the case of light rainfall events rich in organic matter. The part originating from sewer sediment deposits provides a large proportion of organic matter mass. By analysing the content and the volume of sewer deposits at different points from upstream to downstream, it emerges that the main source of this contribution is probably located in man-entry sewers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Therefore, alternative solutions have been studied aimed at using the online storage capacity of the drainage system and at reducing runoff pollution by sedimentation [2][3][4][5]. In particular, the selected option points at separating solid matter of natural origin from the urban one by building silt traps at the main inlets of the local streams.…”
Section: Hydraulic and Solid-transport Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, alternative solutions have been studied aimed at using the online storage capacity of the drainage system and at reducing runoff pollution by sedimentation [2][3][4][5]. In particular, the selected option points at separating solid matter of natural origin from the urban one by building silt traps at the main inlets of the local streams.…”
Section: Hydraulic and Solid-transport Modellingmentioning
confidence: 99%
“…As well as holding polluting potential in itself, solid material in combined wastewater also represents a means for the conveyance of pollutants attached to the solid particles [1][2][3][4][5]. A portion of approximately 30% of settleable solids consists of organic matter, biomass growing on pipe walls (slime), of which 80% is characterised by an average settling velocity of 0.0028 cm/s.…”
Section: Introductionmentioning
confidence: 99%
“…In a constant environment, the respect for strict procedures gives precise and reliable turbidity data, in the laboratory as well as in situ [ 75 ], with a high frequency acquisition (minute order). Moreover, if this parameter is known as a good indicator of suspended matters in sewage networks [ 76 , 77 , 78 ], the turbidity measurement of fresh waters is influenced by the particle size and shape of SS, the presence of plankton and the presence of dissolved humic substances. Some authors have tried to establish correlations between turbidity and parameters like water level, flow rate, or rain intensity [ 73 , 74 ] without success, excepted in the case of a dilution phenomenon following a short dry period before raining [ 79 ].…”
Section: Optical Monitoring Of Microbial Contamination: Current Mementioning
confidence: 99%
“…Sewer sediments are of major importance for wastewater quality processes in urban drainage systems because of the solids provide a transport matrix for different pollutants [60]. It has been observed that TSS is the main vector for many pollutants such as COD, hydrocarbon, heavy metals, micro-pollutants, etc [61,62,63]. As a consequence, the management of sewer solids is a key component in developing a holistic approach to the design and operation of wastewater systems [64].…”
Section: S E W E R S E D I M E N T S : T H E I R P R O P E R T I E S a G I S -B A S E D T O O L F O R E S T I M A T I N G A C C U M U L mentioning
confidence: 99%